Comparison of Different Techniques for the Preservation and Extraction of Phlorotannins in the Kelp Lessonia Spicata (Phaeophyceae): Assays of Dpph, Orac-Pgr, and Orac-Fl as Testing Methods - Lissi-Gervaso, E (Springer Netherlands, 2016)
Preservation, storage, and safe transport of samples are key factors affecting brown algal phlorotannin (phenolics) quantification, their extraction yield, and antioxidant activity. This is especially relevant when field sampling is carried out in remote areas. The objective of the present study was to evaluate and compare five preservation (frozen control, freeze-dried, silica-dried, oven-dried, and air-dried) and two extraction methods (“rapid” and “traditional” extraction) of phlorotannins in the kelp Lessonia spicata (former Lessonia nigrescens). The antioxidant power of the samples treated with the different drying methods was compared through three different in vitro antioxidant assays: 2,2-diphenyl-1-picrylhydrazyl (DPPH) and oxygen radical absorbance capacity (ORAC) methods, employing fluorescein (ORAC-FL) and pyrogallol red (ORAC-PGR) as target molecules. The results of the testing methods indicated that freeze-drying afforded the best extraction yields of phlorotannins (18–30 % higher than control using frozen material) whereas concentrations from samples dried in silica and oven averaged between 17 and 20 % lower than control. The antioxidant activity of phlorotannins measured using the DPPH test decreased significantly in samples kept dried compared to that in control, with activities varying from 65 (freeze-dried) to 21 % (air-dried). Accordingly, with ORAC-PGR and ORAC-FL indexes, sample preservation employing silica-drying or air-drying caused a high decrease of the antioxidant activity of polyphenols. No differences in both total phlorotannin concentration and antioxidant activity between the two extraction methods were found. © 2015, Springer Science+Business Media Dordrecht.